Of dice and men - Slager, Kelley; Abbey, Francis; McNary, Cameron; Casey, Evan; McNary, Cameron; Evans, Ricardo Frederick; Cavegirl Productions; Leomark Studios (Firm) ([Washington, DC] : Cavegirl Productions, 2014)
The lives of six roleplaying gamer friends are thrown into upheaval when one of them enlists to go to Iraq. --
"A geek movie without the self-loathing."
Based on the play by Cameron McNary.
Originally released as a motion picture in 2014
Evan Casey, Cameron McNary, Ricardo Frederick Evans, Gwen Grastorf, Rebecca A. Herron, Greg Thompson
Cinematographer, Autumn Moran ; editor, Kelley Slagle ; music, Noah Potter & Seth C. Polansky.
In English; with English subtitles.
Keywords: Video gamers -- Drama; Fantasy games -- Drama; Friendship -- Drama; Role playing -- Drama; Games -- Design and construction -- Drama; Comedy films; Feature films; Fiction films; Internet videos; Streaming video